Multi-agent-based control strategy for centerless energy management in microgrid clusters - Shi, Shuang; Wang, Yanping; Jin, Jiyu (Frontiers in Energy Research, 2023)
The traditional distribution network dispatching system monitors the microgrid so that most of the distributed power sources are out of control, so it is important to study and innovate the operation mode of microgrid clusters. Firstly, this paper introduces the concepts and advantages of microgrid, microgrid cluster and agent system. Then the research status of microgrid clusters and the structure of multi-agent systems are analyzed. Then, a ring-type multi-agent microgrid cluster structure and a dynamic decentralized compensated energy management strategy are proposed. The method uses a ring-type structure among agents to control the coordinated autonomy of the microgrid cluster. In this approach, agents communicate with each other and microgrid units are electrically interconnected to form a microgrid cluster with stable power output. In addition, the agent system solves the problem of smooth switching of each microgrid. Finally, the simulation platform Matlab verifies the stability of a multi-agent microgrid cluster with energy complementarity.